Pembelajaran Seni Tari untuk Meningkatkan Keterampilan Siswa SD Negeri 2 Padi - Febiyanti Puspitaningrum; Sugiyono; Esti Nur Qorimah (LPPM STKIP PGRI Pacitan, 2024)
Dance is a form of performing art that involves human body movements that are choreographed to convey certain expressions, stories, feelings or messages to the audience. Dance learning is an educational process that aims to teach students about dance, both traditional dance and modern dance. The implementation method consists of several stages, namely the observation and coordination stage of implementation, determination of themes and types of activities, training and documentation stages. The location of this research is SDN 2 Padi located in Watulumbung Hamlet, Padi Village, Tulakan District, Pacitan Regency. Dance learning is an educational process that aims to teach students about dance, both traditional dance and modern dance. The implementation method consists of several stages, namely the observation and coordination stage of implementation, determination of themes and types of activities, training and documentation stages. The location of this research is SDN 2 Padi located in Watulumbung Hamlet, Padi Village, Tulakan District, Pacitan Regency. Dance learning will be held from September 21 to October 23, 2023 with 2-3 meetings a week. There were 17 dance learning participants consisting of 15 women and 2 men from classes IV, V and VI. The results of dance learning include students gaining experience, being able to improve students' skills, fostering self-confidence, and being able to channel their interests and talents in the arts, especially dance